Cotton pads-derived carbon materials/reduced graphene oxide modified with polypyrrole for electrode of supercapacitors - Arias Pinedo, Ofelia M. (2024)
This study investigates the influence of electropolymerization conditions on the deposition of polypyrrole (PPy) onto cotton-derived carbon fiber (CF) modified with reduced graphene oxide (rGO) for supercapacitors applications using an experimental/theorical approach. The surface modification of CF by rGO and/or by PPy electrodeposited at 10, 25 and 50 mV s−1 was thoroughly examined physicochemical and electrochemically. Composite electrodes comprising CF-rGO-PPy, synthesized via electropolymerization at 25 mV s−1, demonstrated a remarkable increase in capacitance, showcasing ∼742 F g−1 compared to 153 F g−1 for CF. SEM, N2-surface area, XPS, and TD-DFT approach revealed that the higher capacitance observed in CF-rGO-PPy electrodes underscores the influence of morphology and charged nitrogen species on the electrochemical performance of these modified electrodes. Notably, this electrode material achieves a specific capacitance retention of ∼96% of their initial capacitance after 10000 cycles at 0.5 A g−1 measured in a two-electrodes cell configuration. This work also discusses the influence of the scan rate used for pyrrole electropolymerization on the pseudocapacitance contribution of PPy and its possible effect on the porosity of the material. These results highlight the importance of appropriate electropolymerization conditions that allow obtaining the synergistic effect between CF, rGO and PPy.